Web-Based API as a Tool in Teaching Computer Vision Concepts - Zacniewski, Artur (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article presents the stages of building Web-based API as a tool for teaching selected concepts of image processing server and shows a structure allowing for its implementation. During the implementation open source tools were used – graphical library OpenCV and Python programming language, which allows the implementation of both web part (by Django framework), as well as the cooperation with the above library. Idea of the creation of new Web-based API endpoints and the ability to change the parameters library OpenCV algorithms by modifying the URL in your browser were shown. Stages of creating each endpoint has been depicted with practical example on the image processing. Advantages and limitations of the proposed solution were presented.
Keywords: Web-based API; Computer Vision; image processing